Manajemen Strategis Koperasi Siswa sebagai Platform Pembelajaran Kewirausahaan di Sekolah Menengah: Studi Kasus di SMA Negeri 1 Palimanan - Ahmad Habibbullah; Yohana Ersi (Journal of Economic and Business Advancement, 2025)
This study examines the strategic management of student cooperatives as a platform for entrepreneurial learning in secondary education, focusing on SMA Negeri 1 Palimanan, Indonesia. The research employs a qualitative descriptive approach to explore how planning, organization, implementation, and evaluation processes contribute to cooperative effectiveness and student skill development. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman’s model. Findings reveal that strategic management practices—supported by collaborative decision-making, transparent financial governance, and regular performance evaluations enhance both operational performance and entrepreneurial competence among students. The cooperative recorded an average annual sales growth of 30%, a 91% participation rate, and balanced profit distribution, indicating effective management and sustainability. Student involvement fosters leadership, teamwork, accountability, and innovation as integral parts of experiential learning. The study concludes that student cooperatives, when managed strategically, serve not only as economic entities but also as practical laboratories for entrepreneurial education that align with the goals of modern, character-based schooling